Faktor Risiko Kejadian Neuropati Diabetik pada Penderita Diabetes Melitus Tipe 2 yang Dirawat Jalan di Poliklinik Penyakit Dalam RS Hikmah Makassar - Hasyim, Hamzah; Wangi, Harakati; Sartika, Suriana Dwi (Bosowa Medical Journal, 2023)
Diabetic neuropathy is a set of nervous disorders and loss of sensory function starting from the distal part of the lower extremities due to high blood glucose in diabetics, which if left unchecked will cause other complications in the form of diabetic ulcers, gangrene, or autonomic cardiovascular neuropathy, with diabetic neuropathy being the complication with the greatest incidence compared to other complications of diabetes. The purpose of the study was to determine the risk factors for the incidence of diabetic neuropathy: (1) nutritional status, (2) triglyceride levels, (3) duration of suffering from diabetes mellitus, (4) controlled blood sugar, and (5) history of hypertension. This study was conducted on 60 people with type 2 diabetes mellitus who were treated on the road at the Internal Medicine Polyclinic of Hikmah Makassar Hospital. This study employed observational and analytical-descriptive methods with a cross-sectional research design, collecting primary data through patient interviews and reviewing medical records of diabetic neuropathy patients at Hikmah Hospital Makassar's Internal Medicine Polyclinic. Data analysis is processed using SPSS software. The results of this study showed that the risk factors for the incidence of diabetic neuropathy in patients with type 2 diabetes mellitus who were treated at the Internal Medicine Polyclinic of Hikmah Makassar Hospital were: (1) A meaningful relationship was obtained between nutritional status and diabetic neuropathy; (2) A meaningful relationship was obtained between triglyceride levels and diabetic neuropathy; (3) A meaningful relationship was obtained between the duration of suffering from diabetes mellitus and diabetic neuropathy; (4) A meaningful relationship was obtained between controlled blood sugar and diabetic neuropathy; and (5) A meaningful relationship was obtained between a history of hypertension and diabetic neuropathy